Model Desa Mandiri Berbasis Ekonomi Syariah di Jawa Timur - Indonesia - Ma'ruf Sya'ban; Fatkur Huda; Arin Setiyowati (BALANCE: Economic, Business, Management and Accounting Journal, 2018)
ABSTRACTThe Sharia economic system has experienced quite good growth and development in Indonesia, this is marked by the rise of Islamic financial institutions and non-bank institutions. Sharia Economic Discourse has become an intensive discussion at seminars and workshops in order to formulate the ideal type of sharia economy. In this regard, Bank Indonesia in collaboration with the Association of Islamic Economics Experts conducted a Sharia-based Independent Village Development Program in East Java. There are several villages used as project pilots in this program, one of them is Cukir Village, Jombang Regency. This research uses a qualitative approach that is a research strategy and technique used to understand the community by gathering as many in-depth facts as possible, and presented in verbal form. The results of this study are the translation of five indicators set by Bank Indonesia related to the assessment of the sharia-based independent village. By translating into the concepts referred to from several references, the concept of an independent village based on sharia economics is found which has an activity value based on sharia principles.Keywords : Independent Village; Sharia Village; Islamic EconomicsCorrespondence to : hudafatkur@gmail.comABSTRAKSistem ekonomi Syariah mengalami pertumbuhan dan perkembangan yang cukup baik di Indonesia, hal ini ditandai dengan maraknya lembaga keuangan syariah maupun lembaga non bank. Wacana Ekonomi Syariah telah menjadi dirkusus yang intensif pada seminar, lokakarya dan workshop guna merumuskan tipe yang ideal ekonomi syariah. Dalam hal ini Bank Indonesia (BI) berkerjasama dengan Ikatan Ahli Ekonomi Islam (IAEI) melakukan program Pengembangan Desa Mandiri Berbasis Ekonomi Syariah di Jawa Timur. Ada beberapa desa yang dijadikan sebagai pilot projek dalam program ini, salah satunya adalah Desa Cukir Kabupaten Jombang. Dalam penelitian ini menggunakan pendekatan kualitatif yaitu strategi dan teknik penelitian yang digunakan untuk memahami masyarakat dengan mengumpulkan sebanyak mungkin fakta mendalam, dan disajikan dalam bentuk verbal. Hasil dari penelitian ini adalah penerjemahan 5 (lima) indikator yang telah ditetapkan oleh Bank Indonesia (BI) terkait penilaian desa mandiri berbasis ekonomi syariah tersebut. Dengan penerjemahan kedalam konsep yang dirujuk dari beberapa refrensi maka ditemukan konsep desa mandiri berbasis ekonomi syariah yang memiliki nilai aktifitas berdasarkan prinsip-prinsip syariah.Kata Kunci : Desa Mandiri, Desa Syariah, Ekonomi SyariahKorespondensi : hudafatkur@gmail.com